PENGARUH FASILITAS BELAJAR DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR TEKNOLOGI PERKANTORAN KELAS X ADP SMK NEGERI 1 LUBUK BASUNG - Adgas Yesa Kriyany; Armiati Armiati (Jurnal Ecogen, 2019)
This study was conducted to determine (1) the effect of learning facilities and learning discipline on student learning outcomes, (2) the effect of learning facilities on student learning outcomes, (3) the effect of learning discipline on student learning outcomes. This research is descriptive and associative causal. The population in this study were class X Office Administration students at SMK N 1 Lubuk Basung with 133 students. The total sample was determined using the Slovin formula and proportional random sampling. From this pattern, 100 students were obtained as research samples. Data collection techniques used in this study were questionnaires and documentation. The instrument of validity test uses Corrected Item-Total Colleration and for reliability testing using alpha coefficient formula. Prerequisite tests were carried out by normality test, heterocedasticity test, and multicollinearity test. The technique used to analyze data is multiple regression analysis. Based on this study, it was found that (1) Learning facilities and learning disciplines had a positive and significant effect on the learning outcomes of Class X Office Technology Office Administration at SMK N 1 Lubuk Basung (2) Learning facilities had a positive and significant effect on learning outcomes in Office X Class Office Administration SMK N 1 Lubuk Basung (3) Learning discipline has a positive and significant effect on the learning outcomes of Class X Office Technology Office Administration at SMK N 1 Lubuk Basung Keyword: Fasilitas Belajar, Disiplin Belajar, Hasil Belajar